The Natural Lift Curve and Geodesic Sprays in Euclidean 4-Space (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
In this work, we presented the natural lift curves of the spherical indicatrices of a curve in E4. Also, some interesting results about the original curve were obtained depending on the assumption that the natural lift curves should be the integral curve of the geodesic spray on the tangentÂ bundle T(S2 ).